Hinterland households: rural agrarian household diversity in northwest Honduras - Douglass, John G., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2002)
The rural sector of agrarian societies has historically been viewed as composed of undifferentiated households primarily interested in self-sufficiency. In more recent times, households have been seen as more diverse than previously thought, both internally (within a single, cooperative unit) and comparatively, but they are still poorly understood. In Hinterland Households, John G. Douglass lays out a new understanding of rural households by investigating the basis of diversity and differentiation as well as the sources for variations in household wealth, production, and size in pre-Colonial Central America. Through the analysis of Late Classic (600-950 a.d.) household sites located in the Naco Valley of northwest Honduras, Douglass tests four competing models of household wealth and production. He evaluates the basis and relative importance of rural household diversity as it relates to social complexity, rural/urban interactions between the center and periphery of Late Classic culture, and access to natural resources.
1. Introduction -- 2. Settlement Patterns, Soil Differentiation, and Agrarian Household Developmental Cycles -- 3. Conceptualizing and Documenting Household Architecture, Activities, and Wealth in the Late Classic Naco Valley -- 4. Small Households: Architecture, Activities, and Wealth -- 5. Large Households: Architecture, Activities, and Wealth -- 6. Household Comparisons: A Return to Research Questions -- 7. Conclusions.
Keywords: Mayas -- Antiquities; Mayas -- Agriculture; Households -- Honduras -- Naco Valley; Excavations (Archaeology) -- Honduras -- Naco Valley; Social archaeology -- Honduras -- Naco Valley; Land settlement patterns -- Honduras -- Naco Valley; Naco Valley (Honduras) -- Antiquities